Pre-frailty in the elderly and the driver license test for motor vehicles - Maria Helena Lenardt; Susanne Elero Betiolli; Letícia Marie Sakai; Nathalia Hammerschmidt Kolb Carneiro; Maria Angélica Binotto; Dayana Cristina Moraes (Rev Rene)
Objective: to investigate the association between the condition of physical pre-frailty in elderly people and the final results of the driver license test for motor vehicles. Methods: cross-sectional study carried out with 347elderly who underwent driver license tests. A questionnaire and tests were applied, and information on the result of the driver license test was collected. A descriptive statistical analysis and a non-parametric test were performed. Results: 163 (47.0%) were found to be pre-frail, 71 (43.6%) had reduced hand grip strength, 65(39.9%) had reduced level of physical activity and 62 (38.0%), reduced gait speed. The result of the driver test indicated 115 (70.6%) pre-frail elderly to be able to drive with restriction. Pre-frailty was not associated with the results of the driver license test (p = 0.744). Conclusion: although the pre-frail condition was frequent, there was no significant association with the result of the driver test.